Environmental Sustainability Role of Green Technologies - Thangavel, P (Springer, 2015)
Covers different categories of green technologies (e.g. biofuels, renewable energy sources, phytoremediation etc.,) in a nutshell -Focuses on next generation technologies which will help to attain the sustainable development -The chapters widely cover for students, faculties and researchers in the scientific arena of Environmentalists, Agriculturalists, Engineers and Policy Makers The World Environment Day 2012 is prepared to embrace green economy. The theme for 2012 encompasses various aspects of human living, ranging from transport to energy to food to sustainable livelihood. Green technology, an eco-friendly clean technology contributes to sustainable development to conserve the natural resources and environment which will meet the demands of the present and future generations. The proposed book mainly focuses on renewable energy sources, organic farming practices, phyto/bioremediation of contaminants, biofuels, green buildings and green chemistry. All of these eco-friendly technologies will help to reduce the amount of waste and pollution and enhance the nation’s economic growth in a sustainable manner. This book is aimed to provide an integrated approach to sustainable environment and it will be of interest not only to environmentalists but also to agriculturists, soil scientists and bridge the gap between the scientists and policy-makers.